Restructuring the Mathematical Power of Students and Teachers: A Case Study in the Misconceptions of Parallelogram Teaching - Mohamad Aminudin; Imam Kusmaryono; Dyana Wijayanti; Chunyu Ji (Jurnal Pendidikan Progresif, 2024)
Restructuring the Mathematical Power of Students and Teachers: A Case Study in the Misconceptions of Parallelogram Teaching. Objectives:  This research aims to (a) investigate cases of misconceptions about understanding parallelograms in mathematics learning and (b) restructure the mathematical power of teachers and students in understanding the concept of parallelograms. Methods: This research is a case study that analyzes in-depth cases of misconceptions in parallelogram learning. The data collection methods are surveys and interviews. This survey involved 120 students and ten teachers as respondents. In the final data analysis, the researcher conducted confirmation and triangulation to ensure the credibility of the findings and conclusions. Findings: The study's findings indicate ontological misconceptions about parallelograms in mathematics learning in elementary and high schools. Students and teachers experience two types of misconceptions, namely preconception errors and modeling errors. Conclusion: The conclusion states that students and teachers have successfully corrected misconceptions through knowledge or mathematical power restructuring so that students and teachers can understand the concept of parallelograms. The process of restructuring mathematical power is characterized by cognitive conflict, scaffolding, and cognitive balance in their thinking processes (teachers and students). The implication is that teachers must correctly instill conceptual knowledge about parallelograms through project-based or inquiry-based learning strategies so that students can build their knowledge based on their learning experiences.Keywords: case study, mathematical power, misconception, parallelogram.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202486